1973
DOI: 10.1063/1.1679138
|View full text |Cite
|
Sign up to set email alerts
|

Cation self-diffusion in single-crystal MgO

Abstract: Cation self-diffusion coefficients have been obtained for MgO in an argon atomosphere over a temperature range 1000–2400°C from concentration gradients determined with the aid of mass spectrometry. The problems associated with use of the short-lived radioisotope 28Mg were avoided by employing the stable isotope 26Mg as a tracer. Samples were prepared utilizing vapor-exchange, thick-film, and semi-infinite source boundary conditions at high, intermediate, and low temperatures, respectively, and were protected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…Both CaO and MgO have Schottky defects, and cations diffuse faster than oxygen. [12][13][14] Hence, one can expect that the oxide scale would primarily form by the outward diffusion of Mg and Ca under normal conditions. In reality, since the Pilling-Bedworth ratios of MgO and CaO were 0.81 and 0.64, respectively, 15) these oxides could not form a compact layer and systematic fissuring occurred as oxidation progressed.…”
Section: Resultsmentioning
confidence: 99%
“…Both CaO and MgO have Schottky defects, and cations diffuse faster than oxygen. [12][13][14] Hence, one can expect that the oxide scale would primarily form by the outward diffusion of Mg and Ca under normal conditions. In reality, since the Pilling-Bedworth ratios of MgO and CaO were 0.81 and 0.64, respectively, 15) these oxides could not form a compact layer and systematic fissuring occurred as oxidation progressed.…”
Section: Resultsmentioning
confidence: 99%
“…This is reminescent of a situation encountered during a study of the model insulator MgO and its electrical conductivity as a function of temperature [Kathrein and Freund, 1983]. MgO had long been considered an excellent insulator up to temperatures above 700øC, the onset of ionic conductivity [Sempolinski and Kingery, 1980;Wuensch et al, 1973]. There were hints of an unusual orders of magnitude increase in the conductivity in the 400-700øC interval but nobody pursued these leads because it could be shown that this enhanced conductivity was confined to the surface and therefore looked like being caused by some kind of "dirt."…”
Section: Recapitulationmentioning
confidence: 99%
“…Early calculations were carried out using classical interatomic potentials (Catlow 1977;Mackrodt & Stewart 1979;Catlow & Stoneham 1983;Bush et al 1994) and the resulting defect formation energies gave reasonable agreement with experimental measurements (Oishi & Kingery 1960;Barr & Lidiard 1970;Hashimoto et al 1972;Wuensch et al 1973;Cohen & Gordon 1976). In recent years, the classical *Author for correspondence (d.duffy@ucl.ac.uk).…”
Section: Introductionmentioning
confidence: 99%